Diagnosis of chronic pancreatitis by measurement of lactoferrin in duodenal juice. Issue 5 (May 1981) - Multigner, L; Figarella, C; Sarles, H
Abstract : Lactoferrin is a non-enzymatic secretory protein of human pancreas and is specifically increased in pancreatic juice of patients with chronic pancreatitis. Duodenal contents being easier to obtain than pure pancreatic juice, the possibility of using lactoferrin measurement in duodenal juice as a diagnosis test for chronic pancreatitis was explored. Forty-eight patients were studied. Duodenal juice was obtained devoid of salivary contamination by a special double lumen tube. Under these conditions lactoferrin secretion (concentration and output) is increased in patients with chronic pancreatitis. When expressed as the ratio of lactoferrin to lipase units, there was no overlap between chronic pancreatitis and other pancreatic disease or controls. The simplicity and the reproducibility of the technique on a material as readily available as duodenal juice confirms the diagnostic value of lactoferrin measurement in the assessment of patients with suspected pancreatic disease.